Youtube czy Studytube – overview of selected profiles about teaching Polish as a foreign language - Kaźmierczak, Paulina; Sroka, Jakub (Activation-innovation-inspiration in (glotto) didactics, 2022)
The article discusses the using of YouTube as a tool for teaching and learning Polish as a foreign language. 23 YouTube channels were analyzed in detail, which at least half of them were conducted in Polish. The aim of the study was to verify the information about the authors, languages used in the films, the number of videos, subscriptions, and the regularity and quality of the presented content. The article also indicates some gaps in technical, substantive or thematic development. Potential actions to fill the niche were also proposed.